Analysis of Added Value and Postharvest Handling Strategies for Corn: A Case Study of UD. Resky Soppeng - Rismayanti; Rosada, Ida; Nurliani; Rasyid, Rasmeidah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aimed to describe the activities involved in postharvest handling of corn, analyze the yield, assess the added value generated, and develop strategies for improving postharvest handling by UD Resky Soppeng in Moncongloe District, Maros Regency. Conducted from February to April 2024 at UD Resky Soppeng, Moncongloe Village, primary data were collected through interviews, observations, and documentation. The data were analyzed using descriptive, yield, added value, and SWOT analyses. The findings reveal that postharvest handling involves purchasing directly from farmers, followed by drying, sorting, milling, packaging, storage, and marketing. The yield rate achieved was 77.77%, indicating high efficiency in the process. The added value generated was IDR 275, with a ratio of 6.44%, showing that UD Resky Soppeng effectively adds value in corn processing. The recommended development strategy is diversification, leveraging internal strengths to address and mitigate external threats.